Depresión y su influencia en el rendimiento académico de una adolescente - Pereira Peñafiel, Genesis Iraida (2020)
Currently, the issue of depression in young students has become the center of interest for many investigations, due to the great negative impact it has in different contexts such as social, personal and educational, it is for this reason that this research, gives to know, what are the most common causes of depression, whether or not these affect the academic performance of adolescents or in what way through a study and clinical follow-up this disorder can be countered that increasingly affects young people . However, to determine the causes that cause depression it is important to make the appropriate study to the patient, take into account the personal, pathological, family history and know the situation of the current problem of the person to be diagnosed